Male victims, experiences with seeking help from domestic violence agencies over time and across western English-speaking countries - Denise A. Hines; Alexandra Lysova; Emily M. Douglas (Journal of Men's Health, 2025)
Background: Male victims of intimate partner violence (IPV) represent a substantial but overlooked portion of IPV victims. Access to domestic violence (DV) services remains a challenge, particularly when agencies primarily serve female victims. This study examines male IPV victims’ experiences with mainstream and specialized DV agencies across four English-speaking regions: the United States, Canada, the United Kingdom/Ireland, and Australia/New Zealand. Methods: Two samples of male IPV victims from Western English-speaking countries/regions were recruited: one consisting of self-identified male IPV victims (n = 594) and the other of male IPV victims from crowdsourcing sample (n = 1380). Participants completed an anonymous online questionnaire, and among other issues, reported on their help-seeking from DV agencies, specific experiences with DV agencies, and perceived helpfulness of the DV agencies’ services. Results: Men from the victims sample were significantly more likely to seek help compared to male IPV victims from the crowdsourcing sample. Specialized DV agencies were rated as more helpful than mainstream agencies. USA respondents reported the most positive experiences, while those from other regions, particularly Canada and the UK/Ireland, reported negative encounters. Conclusions: Findings highlight the need for improved, gender-inclusive training and resources within mainstream DV agencies, as well as increased support and expansion of specialized services for male IPV victims. Policymakers and service providers must address the systematic gaps in support to ensure male victims are recognized and effectively helped across all regions.